Glutaric aciduria type III: A distinctive non-disease? - Knerr, Ina M.; Zschocke, Johannes; Trautmann, U.; Dorland, L.; Koning, T. J. de; Müller, P.; Christensen, E.; Trefz, F. K.; Wündisch, G. F.; Rascher, W.; Hoffmann, Georg F. (Journal of inherited metabolic disease, 2002)
Glutaric aciduria type III is a rare metabolic abnormality leading to persistent isolated glutaric acid excretion. We report the clinical and biochemical phenotypes of three affected children. The first patient is a boy with dysmorphic features and a chromosomal deletion (monosomy 6q26-qter) in whom a persistent glutaric aciduria (500 mmol/mol creatinine, normal <10) was detected during a routine metabolic investigation. The second boy suffered from acute gastroenteritis and hyperthyroidism, when an excessively high urinary glutaric acid excretion was identified (1460 mmol/mol creatinine). The third patient is a girl with constantly elevated glutaric acid in her urine (290 mmol/mol creatinine) but no symptoms of significant disease. In all our patients, glutaric aciduria type I (glutaryl-CoA dehydrogenase deficiency), glutaric aciduria type II (multiple acyl-CoA dehydrogenation defect), and secondary forms of glutaric aciduria (for example due to intestinal infections or mitochondrial dysfunction) could be excluded. Loading with the precursor amino acid lysine in all patients as well as with pipecolic acid in the third case led to an increase in urinary glutaric acid excretion, proving the endogenous origin of glutarate. Glutaric aciduria type III (a defect reported to be caused by peroxisomal glutaryl-CoA oxidase deficiency) is our presumptive diagnosis. However, peroxisomal glutaryl-CoA oxidase is not well characterized and no reliable approach for the direct determination of this enzyme is available to us. To our knowledge, in the English language literature only a single patient with glutaric aciduria type III has been described. Our cases reported here confirm the earlier assumption that glutaric aciduria type III is not related to a distinctive phenotype. Glutaric aciduria type III appears to be a rare metabolic abnormality, presumably of peroxisomal metabolism. However, its pathophysiological impact still needs further investigation.
Gesehen am 21.12.2020